Antecedents of Satisfaction and The Influence of Recommend Intention - Djakasaputra, Arifin; Juliana, Juliana; Lemy, Diena Mutiara; Pramezwary, Amelda; Hubner, Ira Brunchilda; Prabowo, Gunawan (Jurnal Ilmiah Global Education, 2024)
Visitor satisfaction is an important factor in tourist destinations. Therefore, the aim of this research is to test destination image, Emotional experience, Pro-Growth Destination Authenticity, satisfaction and influence on Recommend Intention. The population of this research is tourists visiting Bali. The sample in this study was 200 respondents using a purposive sampling technique with criteria of age 17 years above. tourists visiting tourist villages a minimum of once a year. This research is quantitative research with a survey method. The data collection tool in this research used a questionnaire. Data analysis using PLS-SEM. The research results show that the variables pro growth Destination Image, Pro Growth Destination Authentication, Emotional Experience have a positive and significant influence on satisfaction, and Satisfaction has a positive and significant influence on intention to recommend.